SISTEM INFORMASI E-DELIVERY UNTUK KATEGORI BISNIS SELLER TO CUSTOMER MENGGUNAKAN LARAVEL - Yanto, Yanto; Ridho, M.Rasit (Computer Science and Industrial Engineering, 2024)
The digital era has transformed has transformed the business landscape, including the delivery industry from seller to customer. Batam city, as a growing business hub, is the focus on this research. This transformation demands an efficient e-delivery information system to improve the delivery process and meet competitive market demands. This study aims to design and implement an efficient e-delivery system and understand the challenges in Batam City. The research focuses on couriers operating in Batam, particularly “Delivery Order Batam”. The method used is Design Sprint, which includes context understanding, solution sketching, decision making, prototyping, and user testing. A SWOT analysis evaluates the current delivery service, identifying communication limitations, address locating difficulties, and unmet expedited delivery requests. Based on this analysis, the proposed system aims to optimize the delivery process, overcome courier challenges, improve efficiency, strengthen reputation, and reduce losses due to lost items. This research aims to be contribute to understanding and improving the delivery process in Batam City and inspire similar developments in other regions.